Applicability of remote sensing technologies in the detection and mapping of prosopis spp species: a systematic review: a systematic review - Santos, Patrício Rinaldo dos; Zangalli, Charline; Pinto, Eduardo Luiz Costa Tobias; Alexandre, Fernando da Silva; Fanola, Hannah Cristina Botelho Lima de; Lombardi, Kátia Cylene; Cavalcanti, Maria Luíza Coelho; Ramos, Renilson Pinto da Silva; Libombo, Sérgio Elias; Moura, Magna Soelma Beserra de; Ávila, Fabrício William de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2025)
Remote sensing plays a crucial role in the detection of invasive alien species. This study aimed to explore and present the existing literature on the use of remote sensing technologies for the detection of invasive Prosopis spp canopies in semiarid environments over a long period. A total of fifty studies spanning twelve years were analyzed using the Google Scholar and Science Direct databases, with the help of the ResearchGate social network of researchers and Excel software for data visualization, including word clouds and other graphical representations. The research carried out between 2017 and 2021 witnessed a significant increase in the application of geotechnologies such as Sentinel, LiDAR and hyperspectral images. Vegetation indices, including the Normalized Difference Vegetation Index (NDVI), were widely used. Africa emerged as the continent with the highest level of concern regarding the species discussed, which is evident from the publication of 28 studies. The data revealed that Prosopis juliflora showed greater invasive potential in America and Asia. However, African countries, including Kenya, Ethiopia, Somalia and Sudan, faced a high risk of invasion. The terms found most frequently in the analysis were Prosopis and juliflora. It is essential to prioritize research focused on the application of remote sensing geotechnologies, especially in semiarid regions, to enable informed decision-making by government environmental agencies in relation to the management and control of these invasive species.